Effects of traditional games on age equivalent scores of locomotor and manipulative skills among early stage school children - Abdullah, Borhannudin; Amri, Saidon (Human Resource Management Academic Research Society, 2018)
Purpose: The development of gross motor skills are fundamental to advanced movements and specific skills in sports. Gross motor skills development that are in line with chronological age allows children to master locomotor and manipulative skills well through physical activities. This study aims to determine the effect of physical activity (traditional games) to increase the level of age equivalent locomotor scores (AEL) and age equivalent manipulative scores (AEM) among FELDA’s school children. Methods: This study uses two different modules as the instruments to measure their level of age equivalent. The study involves two phases: (i) descriptive analysis to determine the level of age equivalents and (ii) MANOVA and MANCOVA analysis. Gross motor development data were determined using the Test of Gross Motor Development (TGMD) obtained from video recordings of locomotor and manipulative skills. Findings: The findings of the first phase of the study showed significant delay among Year Three students by 2.13 years of age equivalent locomotors scores (AEL) as compared to Year One and Year Two students who showed delay in their age equivalent manipulative scores (AEM) by 2.62 years. MANOVA analysis showed a significant difference in the mean GMDQ for pretest [ F ( 3.60 ) = 3:39 ; p <0.05 , R2 = .145 ] and post-test [ F ( 3.60 ) = 40.28 : p <0.01 , R2 = .668 ] between control and treatment groups. Furthermore, F univariate analysis showed significant differences for the three dependent variables during the post-test on their GMDQ [ F ( 1,62 ) = 116.16 ; p <0.001 , R2 = .65 ] , AEL [ F ( 1,62 ) = 36.53 ; p < 0.001 , R2 = .37 ] , and AEM [ F ( 1,62 ) = 48.76 : p <0.001 , R2 = .44 ]. MANCOVA analysis showed a significant difference for mean of gross motor development [F(4,58) = 29.80; p<0.001, eta squared = 0.673] for both groups even though the pre-test scores were controlled. The researchers deduced that Traditional Games explained 67.3% variance in the mean for gross motor development. Conclusion: Intervention programs that utilise traditional games can improve the age equivalent locomotors scores (AEL) and age equivalent manipulative scores (AEM) among Felda school children.